2012
DOI: 10.2337/dc12-0669
|View full text |Cite
|
Sign up to set email alerts
|

Projections of Type 1 and Type 2 Diabetes Burden in the U.S. Population Aged <20 Years Through 2050

Abstract: OBJECTIVETo forecast the number of U.S. individuals aged <20 years with type 1 diabetes mellitus (T1DM) or type 2 diabetes mellitus (T2DM) through 2050, accounting for changing demography and diabetes incidence.RESEARCH DESIGN AND METHODSWe used Markov modeling framework to generate yearly forecasts of the number of individuals in each of three states (diabetes, no diabetes, and death). We used 2001 prevalence and 2002 incidence of T1DM and T2DM from the SEARCH for Diabetes in Youth study and U.S. Census Burea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
281
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 430 publications
(300 citation statements)
references
References 28 publications
2
281
0
10
Order By: Relevance
“…4 (18), which may at least partially explain the increase in prevalence of type 1 diabetes seen in this study. Obesity is the most important risk factor for type 2 diabetes in youth, and the rise in pediatric obesity was accompanied by an increased prevalence of type 2 diabetes in children (19,20). Based on the National Health and Nutrition Examination Survey, Ogden et al S. youth remained stable and even decreased among children aged 2-5 years, which may at least partially explain our findings on the prevalence of type 2 diabetes.…”
Section: Prevalence Of Diabetic Nephropathymentioning
confidence: 55%
“…4 (18), which may at least partially explain the increase in prevalence of type 1 diabetes seen in this study. Obesity is the most important risk factor for type 2 diabetes in youth, and the rise in pediatric obesity was accompanied by an increased prevalence of type 2 diabetes in children (19,20). Based on the National Health and Nutrition Examination Survey, Ogden et al S. youth remained stable and even decreased among children aged 2-5 years, which may at least partially explain our findings on the prevalence of type 2 diabetes.…”
Section: Prevalence Of Diabetic Nephropathymentioning
confidence: 55%
“…Some researchers have suggested a 26% increase in risk for men than women20. The increasing incidence has been attributed ecologically to an increasing prevalence of central obesity, total dietary intake, a shift in the ratio of refined vs unrefined carbohydrates and simple sugars, increased portion sizes, and decrease in energy expenditure21, 22. In 2005–2009, the prevalence was 13.6% in women and 9.8% in men, which is not similar to the results of the study reported by Yang et al 5…”
Section: Discussionmentioning
confidence: 86%
“…The incidence is rising steadily, particularly for younger children, and projections suggest nearly a tripling of T1DM from 2010 to 2050 [2]. Despite on-going technological advances, the majority of affected patients are not able to achieve recommended glycemic targets [3].…”
mentioning
confidence: 99%